2017
DOI: 10.1111/aos.13389
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring daily intraocular pressure fluctuations with self‐tonometry in healthy subjects

Abstract: Rebound self-tonometry appears to be accurate and could be used to monitor short- and long-term IOP variations. The difference between IOP patterns on consecutive days raises questions as to the certainty of a single IOP measurement as a measure of treatment effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 24 publications
4
20
1
Order By: Relevance
“…It aims to record diurnal changes of IOP and detect any IOP spikes that occur outside office hours. Several studies reported Icare rebound tonometry to be valuable in managing paediatrics and adult patients . It is well‐tolerated by the majority of patients and offers reliable IOP measurement which correlates with the GAT …”
Section: Introductionmentioning
confidence: 99%
“…It aims to record diurnal changes of IOP and detect any IOP spikes that occur outside office hours. Several studies reported Icare rebound tonometry to be valuable in managing paediatrics and adult patients . It is well‐tolerated by the majority of patients and offers reliable IOP measurement which correlates with the GAT …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, self-administered rebound tonometry performed without topical anaesthesia has been investigated for use in diurnal intraocular pressure monitoring. 21 , 22 First, the iCare ONE and more recently the iCare HOME (iCare Finland Oy, Vantaa, Finland) have demonstrated good repeatability and correlation with Goldmann applanation tonometry in both healthy persons and glaucoma patients. 23 26 With appropriate training and instruction, most patients were able to successfully perform self-tonometry with the advantage of obtaining intraocular pressure measurements in the patient's habitual environment and fewer visits to the health practitioner's office.…”
mentioning
confidence: 99%
“… 24 , 25 Previous reports investigating diurnal intraocular pressure with rebound self-tonometry have demonstrated high intraindividual variation across consecutive days, with participants exhibiting different diurnal curve patterns from day to day. 21 , 22 However, no studies to date have investigated diurnal curve fluctuations with iCare HOME for more than a week.…”
mentioning
confidence: 99%
“…Thanks to the up come of a new self-tonometer, iCare Home Ò , ophthalmologists have now the possibility to gather more information on the IOP. Many studies have shown that iCare Home Ò is a reliable device (Tarkkanen et al 2010;Chen et al 2016;Pronin et al 2017;Querat & Chen 2017;Tarkkanen & Kivela 2018). Motivated patients or a suitable accompanying person can be trained to perform home tonometry.…”
mentioning
confidence: 99%